Absorption of nutrients by cowpea irrigated with saline water under different leaching fractions - Cristiano Tagliaferre; Diogo U. G. Guimarães; Lorena J. Gonçalves; Carlos H. F. Amorim; Willian V. Campos; Felizardo A. Rocha (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Salinity is one of the main environmental problems that negatively affect plant growth and metabolism, besides being one of the factors responsible for the decrease in the yield of crops, especially in arid and semiarid regions. Thus, the aim of this study was to evaluate the effects of soil salinity on the mineral nutrition of irrigated cowpea. The experiment was conducted in drainage lysimeters in a greenhouse, in a completely randomized design with seven treatments, one irrigated with freshwater (control) and six irrigated with saline water with different leaching fractions (5, 10, 15, 20, 30 and 40%) of the applied irrigation depth, with three replicates. The irrigation with saline water treatments did not affect significantly the contents of macronutrients and Na in the cowpea leaves, while the opposite behavior occurred with the micronutrients.